The Role of Synergetics in Supporting Human Life - Kuvandikovich, Kuvandikov Oblakul; Turatovich, Usarov Uktam (European Journal of Life Safety and Stability (2660-9630), 2022)
The paper presents synergetics, which is a new interdisciplinary science that studies the basic laws of self-organization of complex systems. It includes such areas as nonlinear dynamics, chaos, fractals, catastrophes, bifurcation, waves, solitons, field effects, etc. The application of synergetic methods to the analysis of natural phenomena and cataclysms is shown